Posttraumatic Reactions to Psychosis: A Qualitative Analysis - Lu, Weili; Mueser, Kim T.; Rosenberg, Stanley D.; Yanos, Philip T.; Mahmoud, Neisrein (Frontiers in Psychiatry, 2017)
The current study aimed to evaluate the potentially traumatic aspects of psychotic symptoms and psychiatric treatment of psychosis using qualitative methods. Participants included 63 people with First Episode Psychosis or multiple psychotic episodes. Quasi-structured interviews were used to explore those aspects of symptoms and treatment that were perceived as traumatic Emotional reactions to the most traumatic aspect of symptoms and treatment, during and after the event, were also examined. Participants described a number of traumatogenic aspects of psychotic symptoms, including frightening hallucinations; suicidal thought/ attempts, thoughts/ attempts to hurt others; paranoia/delusions and bizarre/disorganized behavior or catatonia. Traumatic aspects of psychosis elicited emotions including anger, sadness and confusion, anxiety and numbness at the time of event. Furthermore, many participants found aspects of treatment to be traumatic, including: being forced to stay in the hospital for a long time; experiencing upsetting side-effects; coercive treatments, including involuntary hospitalization, use of restraints, and forced medication; being exposed to aggressive patients; and mistreatment by professionals. These experiences elicited emotions of anger, sadness, distrust, and a sense of helplessness. Study findings suggest that the experiences both of psychotic symptoms and psychiatric treatment are potentially traumatic can be a powerful barrier to engaging people in mental health services and facilitating recovery. Clinical implications were discussed. Keywords: Trauma, Psychosis, PTSD, Treatment